2012
DOI: 10.1155/2012/768456
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Physiotherapy and Occupational Therapy after Traumatic Brain Injury in the Intensive Care Unit

Abstract: Physiotherapy and occupational therapy are frequently administered in intensive care units (ICUs) after traumatic brain injury (TBI) to promote recovery. The increasing economic pressure and the growing need for evidence of therapeutic effectiveness are reasons for reviewing the currently available scientific data. The databases of OTseeker, PEDro, Medline, and Cochrane were searched for studies on frequently applied therapeutic procedures in the ICU following a TBI. It becomes evident that the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 33 publications
0
20
0
4
Order By: Relevance
“…Our results highlight the problem of lack of homogeneity of the contents of rehabilitation in the ICU at this time. The literature suggests that rehabilitation in the ICU for sABI patients is primarily focused on respiratory therapy, passive-assistive movement for contracture prophylaxis, stimulation therapy, low-dose strength, and endurance training and stretching (36). The therapeutic goal is usually focused on the prevention of secondary damage (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Our results highlight the problem of lack of homogeneity of the contents of rehabilitation in the ICU at this time. The literature suggests that rehabilitation in the ICU for sABI patients is primarily focused on respiratory therapy, passive-assistive movement for contracture prophylaxis, stimulation therapy, low-dose strength, and endurance training and stretching (36). The therapeutic goal is usually focused on the prevention of secondary damage (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the professional coordinate the rehabilitation therapy, considering the results of the assessment. For this, some specific physiotherapeutic methods showed positive effects on patients with TBI and can be recommended, such as mobilization, sensory stimulation, fitness or aerobic training, respiratory therapy, contracture prophylaxis and functional training (sit-to-stand, gait and arm ability training) [4,9]. These different methods for treatment are chosen for many different reasons by the physiotherapists, but the most important is to choose based on the patient's problems.…”
Section: Physical Rehabilitationmentioning
confidence: 99%
“…These patients can experience long-term physical, cognitive, behavioral, and emotional consequences [2] due an extremely varied spectrum of possible lesions, resulting in many potential disabilities [3]. Furthermore, each person has a different set of premorbid abilities and a different psychosocial situation [3] that leads to a high degree of heterogeneity in the manifestation of clinical symptoms and makes the treatment of the accident victims particularly challenging [4]. Because of this, the rehabilitation process needs to be carefully planned and the goals need to be holistic, long term and individualized to each survivor and his or her family [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SLPs play a vital role in the management of TBI (Porter, Constantinidou, & Marron, 2014) Although previous research (Hellweg, 2012) has shown that patients who receive therapy demonstrate earlier functional improvements, more research is needed to understand the complex, heterogenous effects of TBI and determine specific evidencebased practices (Watson, 2001;Shiel, Burn, & Henry, 2001;Slade, Tennant, & Chamberlain, 2002;Turner-Stokes, Disler, Nair, & Wade, 2005;Zhu, Poon, Chan, & Chan, 2007;Zhu, Poon, Chan, & Chan, 2001). Further, present research reflects limited understanding of the educational and training needs of rehabilitation professionals, warranting further investigation of this topic.…”
Section: Rehabilitationmentioning
confidence: 94%
“…During rehabilitation, OTs provide interventions to improve arousal and alertness, improve motor function, improve occupational performance, visualperceptual, behavioral or emotional impairments, and improve performance of everyday activities, occupational duties and social participation (Wheeler & Acord-Vira, 2016). Like PT, OT services may be provided through in-and out-patient rehabilitation programs, as well as hospital ICUs to promote recovery following TBI, with common treatments including sensory stimulation and activities of daily living (ADL) training (Hellweg, 2012).…”
Section: Rehabilitationmentioning
confidence: 99%